Biosurfactant surfactin as a kinetic promoter for methane hydrate formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Pradhan, Darshan; Naik, Rajesh; Zare, Kirti; Mawlankar, Rahul R.; Dastager, Syed Gulam; Kushwaha, Omkar Singh; Kumar, Rajnish (Energy Procedia, 2017)
In the present study, the effect of the biosurfactant Surfactin on methane hydrate formation kinetics was studied. Initially, several marine derived species were screened for the presence of Surfactin. The polymerase chain reaction technique was used as the preliminary screening step for Surfactin which was then followed up by a couple of different assays to provide conclusive evidence of the same. Based on these tests, the D-9 bacterial strain was identified as a producer of Surfactin. Once the presence of Surfactin had been proven, its effect on methane hydrate formation kinetics was investigated upon by carrying out hydrate formation experiments in a stirred tank reactor. The cell free supernatant containing Surfactin was itself used as the hydrate forming solution without any further processing. It was found that the presence of Surfactin in the system greatly enhances hydrate formation kinetics as compared to pure water. In fact the kinetics in presence of Surfactin also surpassed that obtained with 1 wt% SDS, the most commonly used synthetic kinetic hydrate promoter. This basic study can pave the way for more sophisticated research on the use of biosurfactants as kinetic promoters with a view on rapid methane hydrate formation kinetics for applications such as methane separation, storage and transport.